PENGARUH MODAL SOSIAL DAN LEADER MEMBER EXCHANGE TERHADAP KINERJA MELALUI KOMITMEN ORGANISASIONAL - R.M. Firdaus R.M. Firdaus (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2017)
This study aimed to find out the effects of Social Capital and LMX (leader member exchange) on the Performance through Organizational Commitment studies on Kisnala Batik Pekalongan firm. The population of this study was all employees ofKisnala Batik Pekalongan with the number of 150 people. This study usedproportional random sampling which is a way of sampling by selecting each sampling unit in accordance with the size of the sampling unit so that the sample became 100 people. The hypothesis testing was done by using direct and indirect hypothesis test or mediation test. Based on the study, the results showed that:The effects of Social Capital on Organizational Commitment were insignificant, Leader Member Exchange (LMX) had significant and positive impact on Organizational Commitment., Social Capital had a significant and positive impact on Performance, The effects of Leader Member Exchange (LMX) on the Performance were insignificant.,Organizational Commitment had significant and positive impact on Performance. Keywords: Social Capital, Leader Member Exchange (LMX), Performance, and Organizational Commitment